2009
DOI: 10.1097/mbc.0b013e3283254549
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde and coenzyme Q10 in platelets and serum in type 2 diabetes mellitus: correlation with glycemic control

Abstract: This study investigated the level of platelet malondialdehyde (MDA) as a marker of oxidative stress and coenzyme Q10 (CoQ10) as an index of antioxidant capacity in patients with type 2 diabetes mellitus and their relation to glycemic control. The study group consisted of 28 patients with type 2 diabetes mellitus (10 men and 18 women) with mean age of 48 +/- 2 years. Ten healthy individuals, age and sex matched with the patients, were used as a control group. Laboratory investigations in the form of lipid profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 17 publications
3
25
0
1
Order By: Relevance
“…In a mutual scenario, Anderson et al [56] stated also that AGEs may be generated by oxidative stress and inflammation, where MPO can trigger the production of RAGE ligands by generating different stresses, including NF-kB, which begets further inflammation and an endless cycle of AGE production. This fact was imitated herein by the marked activation of MPO, decreased GSH level and the 2 fold elevation of the lipid peroxide product and as documented previously [57], [58]. These results suggest that hyperglycemia may bridge the ligand-RAGE axis upregulation with increased oxidant stress and inflammation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a mutual scenario, Anderson et al [56] stated also that AGEs may be generated by oxidative stress and inflammation, where MPO can trigger the production of RAGE ligands by generating different stresses, including NF-kB, which begets further inflammation and an endless cycle of AGE production. This fact was imitated herein by the marked activation of MPO, decreased GSH level and the 2 fold elevation of the lipid peroxide product and as documented previously [57], [58]. These results suggest that hyperglycemia may bridge the ligand-RAGE axis upregulation with increased oxidant stress and inflammation.…”
Section: Discussionsupporting
confidence: 85%
“…This fact explains the restoration of GSH and the decrease of lipid peroxidation proved by the current model and others [57], [58], in addition to the inhibition of MPO and the elevation of sRAGE. In a vicious cycle, the CoQ10-mediated sRAGE elevation adds to its antioxidant mechanisms, where inhibition of AGE/RAGE axis entails an elevation in sRAGE and a decrease in the production of ROS [55].…”
Section: Discussionsupporting
confidence: 81%
“…In a study on diabetes-induced rat model where Coenzyme Q10 (CoQ10) was compared with α lipoic acid (ALA), the CoQ10 proved to stop the shift of actively contributing nerve fibers toward slower conduction velocities and tended to restore velocities of sciatic nerves toward those of the age-matched control group, whereas ALA did not produce statistically significant effects [145]. Clinical observation of endogenous CoQ10 has shown that, in type 2 DM patients, plasma and platelet MDA, as a marker of oxidative stress, were significantly higher, and the level of CoQ10, as antioxidant capacity, was significantly lower compared to controls, with a negative correlation between plasma CoQ10 and HbA1c [146]. When patients with type 2 DM and DPN were supplemented with 400 mg/day of CoQ10, NSS, Neuropathic Disability Score (NDS), and NCS were improved compared to placebo and associated with a reduction in LPO after 12 weeks of treatment [147].…”
Section: Diabetic Polyneuropathymentioning
confidence: 99%
“…6,7 Effect of CoQ10 on blood glucose control Several studies have reported significantly reduced blood CoQ10 levels in type 2 diabetic patients, correlating with increased levels of plasma glucose, HbA1c and markers of oxidative stress. 8 It has been proposed that, in older patients with type 2 diabetes (in whom blood CoQ10 levels have become depleted to 0.35 μg/ml or less) and who have become refractory to hypoglycaemic drugs, supplementation with CoQ10 is most effective; in particular, the subsequent response to hypoglycaemic drugs is significantly improved (W Judy, unpublished data).…”
Section: Coenzyme Q10 (Coq10)mentioning
confidence: 99%